Islamic Law Criticism of Mental Disabilities Marriage - Fadllurrohman Fadllurrohman (Eduvest - Journal of Universal Studies, 2022)
Marriage is the most useful and most important way in effort realize and maintain honor, because with this marriage somebody can awake from what Allah has forbidden. People with disabilities disability as normal human beings who are also blessed desire sexual naturally have desire for tie self in bond marriage . As for goals from study dissertation this is for knowing in a manner in application: Marriage Law For disabled Mental disabilities according to Law No. 8 of 2016, fulfillment obligation wife or husband disabled internal mental disability marriage, implementation marriage disabled mental disability according to the Marriage Law in Indonesia, Review of Islamic Law concerning marriage disabled mental disability. Method research used in writing dissertation this is study library (library research). technique deep data collection study this conducted through studies documentation about marriage disabled originating mental disability from books, articles, magazines, letters news, or source literature other, which later taken conclusion based on these data. kindly general religion of Islam is not once forbid the marriage that took place between disabled mentally handicapped p this remember the goal base marriage that is as means distribute desire sexual with good and true as well as as institution preventive happening wickedness and adultery. However, clan disability in Thing marriage not yet fully protected because they are very risky or susceptible to divorce.